Metode Pembelajaran Dalam Surah An-Nahl Ayat 125 - Julia Elvina; Meylani Eka Putri; Siti Nabila (STIKes Ibnu Sina Ajibarang, 2024)
The greatest way to learn, according to Surah An Nahl verse 125, is to read up on three distinct learning strategies: Bil hikmah (wise), Mauidhotul Hasanah (great instruction), and Jaadilhum Billati Hiya Ahsan (denying it in a constructive way). When presenting truth, wisdom takes into account the listener's situation as well as the current environment and is grounded in reason and science. Virtue is emphasized while vice is forbidden in the practice of mau'idhah hasanah. Jidal is an effort between two people to share ideas and come to a decision without any animosity toward one another.